Is there an optimal training intensity for enhancing the maximal oxygen uptake of distance runners? Empirical research findings, current opinions, physiological rationale and practical recommendations - Midgley, A. W.; McNaughton, L. R.; Wilkinson, M. (Sports Medicine, 2006)
The maximal oxygen uptake (VO2max) is considered an important physiological determinant of middle- and long-distance running performance. Little information exists in the scientific literature relating to the most effective training intensity for the enhancement of VO2max in well trained distance runners. Training intensities of 40-50% VO2max can increase VO2max substantially in untrained individuals. The minimum training intensity that elicits the enhancement of VO2max is highly dependent on the initial VO2max, however, and well trained distance runners probably need to train at relative high percentages of VO2max to elicit further increments. Some authors have suggested that training at 70-80% VO2max is optimal. Many studies have investigated the maximum amount of time runners can maintain 95-100% VO2max with the assertion that this intensity is optimal in enhancing VO2max. Presently, there have been no well controlled training studies to support this premise. Myocardial morphological changes that increase maximal stroke volume, increased capillarisation of skeletal muscle, increased myoglobin concentration, and increased oxidative capacity of type II skeletal muscle fibres are adaptations associated with the enhancement of VO2max. The strength of stimuli that elicit adaptation is exercise intensity dependent up to VO2max, indicating that training at or near VO2max may be the most effective intensity to enhance VO2max in well trained distance runners. Lower training intensities may induce similar adaptation because the physiological stress can be imposed for longer periods. This is probably only true for moderately trained runners, however, because all cardiorespiratory adaptations elicited by submaximal training have probably already been elicited in distance runners competing at a relatively high level. Well trained distance runners have been reported to reach a plateau in VO2max enhancement; however, many studies have demonstrated that the VO2max of well trained runners can be enhanced when training protocols known to elicit 95-100% VO2max are included in their training programmes. This supports the premise that high-intensity training may be effective or even necessary for well trained distance runners to enhance VO2max. However, the efficacy of optimised protocols for enhancing VO2max needs to be established with well controlled studies in which they are compared with protocols involving other training intensities typically used by distance runners to enhance VO2max.